(untitled) (International journal of artificial intelligence, 2026)
This article examines the impact of digital transformation processes on the development of the financial accounting system. In the context of globalization and rapid digitalization, financial accounting practices within organizations are undergoing significant changes, shifting from traditional accounting mechanisms to automated and digitally driven systems. The study highlights the advantages of implementing information technologies in financial accounting, including improved accuracy, timeliness, and transparency of financial data. In addition, particular attention is paid to the challenges associated with digital transformation, such as information security risks, the need for skilled human capital, and the adaptability of accounting systems to technological change. The article provides an analytical assessment of how the integration of digital technologies into financial accounting enhances the quality of managerial decision-making and offers practical recommendations for the effective development of accounting systems in a digital environment.